Blood Levels of Trace Elements, Electrolytes, and Oxidative Stress/Antioxidant Systems in Epileptic Patients - Sherifa A. Hamed; Moustafa M. Abdellah; Nagla El-Melegy (Elsevier, 2004)
Epileptic patients exhibited variably altered status of trace elements, electrolytes, and free radical scavenging enzyme activities. We investigated the effect of epilepsy and long-term antiepileptic drug therapy on the serum level of some trace elements (zinc, selenium, and copper), electrolytes (calcium, magnesium, sodium, and potassium), and antioxidants (glutathione peroxidase, and uric acid) and plasma levels of lipid peroxidation index (malondialdehyde), total antioxidant capacity, and ceruloplasmin. Seventy epileptic patients and fourteen controls were recruited in this study. In the treated group (particularly with valproate), we reported increases in the levels of zinc, calcium, sodium, malondialdehyde, and glutathione peroxidase and decreases in the levels of copper, total antioxidant capacity, and ceruloplasmin with no difference in selenium, magnesium, and potassium. However among untreated epileptics, uric acid level was increased and total antioxidant capacity was markedly lowered. We conclude that the above parameters balance differs in epileptics comparable to controls and hence their correlation to seizures pathophysiology and their degree of control or resistance to antiepileptic drug therapy. Better regulation of the lipid peroxidation and antioxidants and fewer disturbances in mineral metabolism were observed in monotherapy versus polytherapy and with carbamazepine versus valproate therapy. Keywords:: trace element, electrolyte, antiepileptic drug, oxidative stress, antioxidant